Angiogenesis in myelodysplastic syndromes. - Pruneri, G; Bertolini, F; Soligo, D; Carboni, N; Cortelezzi, A; Ferrucci, P; Buffa, R; Lambertenghi-Deliliers, G; Pezzella, F (1999)
It is now well established that solid tumour growth depends on angiogenesis. However, less is known about the generation of new vessels in haematological malignancies and, in particular, in preleukaemic-myelodysplastic syndromes (MDS). In this study, bone marrow microvessel density (MVD) was assessed by immunohistochemistry and compared in trephine biopsies from 14 controls, five infectious disease (ID), 82 MDS, 15 acute myeloid leukaemia (AML) and 14 myeloproliferative disorder (MPD) patients. Statistical analysis (P < 0.001) demonstrated that MDS MVD was higher than in controls and ID (21 +/- 9 vs 6 +/- 2 and 10 +/- 8 respectively) but lower than AML (30 +/- 12) and MPD (40 +/- 12). Among MDS-FAB subtypes, MVD was significantly higher in RAEB-t, CMML and fibrosis subsets compared to RA, RARS and RAEB subsets (P= 0.008). To further investigate angiogenesis machinery, the expression of vascular endothelial growth factor (VEGF) was evaluated by means of immunohistochemistry in control, MDS, AML and MPD biopsies. Even though VEGF mRNA expression was reported in the past in AML cell cultures and cell lines, in our samples VEGF expression was found to be particularly strong in most of the megakaryocytes but significantly less prominent in other cell populations including blasts. Since our findings suggest a correlation between angiogenesis and progression to leukaemia, additional work is now warranted to determine what regulates the generation of new vessels in MDS and leukaemia.